EXAMINATION OF HEALTH SCIENCE UNIVERSITY STUDENTS’ LEVEL OF READINESS FOR E-LEARNING - İbili, Emin (International Online Journal of Education and Teaching, 2020)
In this study, the e-readiness levels of university students studying in the field of health sciences were examined in terms of different variables. In this context, whether the level of e-readiness differs according to gender, department, class level, type of education, device ownership, working status and economic level has been examined. In addition, the relationship between e-readiness level and academic success was investigated. The research sample consists of 923 health science students studying in different departments. The results of the research show that gender, learning type, device type and income level are important factors on the e-readiness level. In addition, the e-readiness levels of the nursing department students, normal (daytime) teaching, 1st year students were found to be low in the study. As the difficulty level of the courses increased, the level of e-readiness was found to be an important factor on academic achievement. The results obtained from this research provide important clues for academicians as well as institutions and organizations providing services in the field of health sciences who want to switch to distance education. In addition, some suggestions were made in the light of this research results. Keywords: E-readiness levels, university students, health science university.